Financial literacy and practices : a case study of entrepreneurs from the informal economic sector in Moshupa village of Botswana - Tlotlo, Matshediso Matoko (2017)
The purpose of this study was to have an in-depth understanding of financial literacy and practices of entrepreneurs from the informal sector in Moshupa rural village of Botswana in the light of the evidence of low literacy levels documented across the world (S&P Global FinLit Survey, 2014). The question then was: If there is such low financial literacy across the world including the developed countries and emerging markets, what is the case in a rural village in a developing country like Botswana? Data for this study was collected by conducting face-to face interviews, questionnaires, observations and listening to participants’ stories about their business operations. The study’s findings are that 83% of the participants perceived themselves to be financially literate however only 60% of participants were able to pass the objective financial literacy test adopted from OECD (2016). The results demonstrate confidence and potential of participants in financial literacy and practice. However they lacked initiative in navigating financial and business challenges as entrepreneurs. Nevertheless, they articulated their contributions towards improved livelihoods in the village. The gaps in basic financial literacy and lack of initiative in navigating challenges imply that mobilisation of entrepreneurs for capacity building in financial literacy through education programmes is needed. Such training would help build the financial capabilities of rural entrepreneurs in the informal sector and enable them to grow sustainable businesses that can lead to improved financial wealth and sustainable livelihoods. Further, research on the level of financial literacy of rural entrepreneurs in the informal sector covering all remote rural villages in Botswana is recommended.